2005
DOI: 10.1007/s11244-005-3793-5
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for oxidation catalyzed by polyoxometalates at the interface of homogeneous and heterogeneous catalysis

Abstract: A basic premise behind the use of polyoxometalates in oxidation chemistry is the fact that polyoxometalates are oxidatively stable. This, a priori, leads to the conclusion that for practical purposes polyoxometalates would have distinct advantages over widely investigated organometallic compounds that are vulnerable to decomposition due to oxidation of the ligand bound to the metal center. Since polyoxometalate synthesis is normally carried out in water by mixing the stoichiometrically required amounts of mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 40 publications
0
63
0
Order By: Relevance
“…The results presented in table 1 (entries [1][2][3][4][5] show that the activity of the Au catalyst is influenced by the type of support used for the oxidation of benzyl alcohol (see figure 1). The initial activity of the catalysts decreases in the order ZSM-5 > b > Y > TiO 2 > TS-1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results presented in table 1 (entries [1][2][3][4][5] show that the activity of the Au catalyst is influenced by the type of support used for the oxidation of benzyl alcohol (see figure 1). The initial activity of the catalysts decreases in the order ZSM-5 > b > Y > TiO 2 > TS-1.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the importance of selective oxidation as a unit process in the manufacture of chemical intermediates [1]. The oxidation of alcohols to aldehydes is a fundamentally important laboratory and commercial procedure [1][2][3][4][5][6][7][8] since the products are valuable both as intermediates as well as being highvalue components for the perfumery industry [1,9,10]. Many selective oxidation reactions are carried out without the use of modern catalytic technology and in such cases these oxidations are effected using stoichiometric oxygen donors, such as chromate or permanganate.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of Au to Pd nanocrystals improved the overall selectivity and, using scanning transmission electron microscopy combined with x-ray photoelectron spectroscopy, we showed that the Au-Pd nanocrystals were made up of a Au-rich core with a Pd-rich shell, indicating that the Au electronically influences the catalytic properties of Pd. S elective oxidation is important in the synthesis of fine chemicals and intermediates (1); and, in particular, the oxidation of primary alcohols to aldehydes is a fundamentally important laboratory and commercial procedure (1)(2)(3)(4)(5)(6)(7)(8). Aldehydes are valuable both as intermediates and as highvalue components for the perfume industry (1,9,10).…”
Section: Solvent-free Oxidation Of Primary Alcohols To Aldehydes Usinmentioning
confidence: 99%
“…The behaviour of TSMP was studied in the number of papers by: Bregeault, Cavani, Kozhevnikov, Kuznetsova, Mizuno, and Vazylyev, who found that TSMP show catalytic activity in oxidation of hydrocarbons in both heterogeneous and homogeneous reactions. However, the majority of studies were concerned with mixed addenda systems [9][10][11][12][13][14][15]. Much less is known about behaviour of TSMP in homogeneous reactions.…”
Section: Introductionmentioning
confidence: 99%